2017
DOI: 10.4236/psych.2017.81001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mindfulness-Based Intervention for Athletes

Abstract: Recently, several top athletes, as well as coaches, have revealed that mindfulness can be regarded as a type of psychological training to optimize performance. Indeed, results of studies in clinical psychology, as well as neuroscience, suggest that mindfulness might be an effective strategy to promote concentration, emotion regulation and state of flow. However, the empirical evidence in the context of sport is rather sparse. The aim of this study was to examine the effectiveness of a mindfulness-based interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Effective mood regulation is highly individualized, with many potential regulation strategies available [74,75]. Some may be effective in the short term (e.g., using music to relax or arouse [76]) and others may have longer term mental health benefits (e.g., relaxation/mindfulness training, yoga [77,78]). Some habitual coping strategies may pose a threat to health (e.g., excessive alcohol consumption [79]) or to performance (e.g., negative self-talk [80]).…”
Section: Recommendation Explanationmentioning
confidence: 99%
“…Effective mood regulation is highly individualized, with many potential regulation strategies available [74,75]. Some may be effective in the short term (e.g., using music to relax or arouse [76]) and others may have longer term mental health benefits (e.g., relaxation/mindfulness training, yoga [77,78]). Some habitual coping strategies may pose a threat to health (e.g., excessive alcohol consumption [79]) or to performance (e.g., negative self-talk [80]).…”
Section: Recommendation Explanationmentioning
confidence: 99%
“…Based on this idea, several emotion-focused approaches for affect regulation have since been developed ( Greenberg, 2011 ; Leahy et al, 2011 ). Within the sports context, similar programs have been developed to improve affect regulation ( Kaufman et al, 2009 ; Jekauc et al, 2016 ). Along these same lines, it has also been shown that mindfulness training, which emphasizes awareness of one’s affective states, leads to improvements in affect regulation skills in athletes ( Kittler et al, 2018 ).…”
Section: Affect Regulation Within the Cycle Of Emotionsmentioning
confidence: 99%
“…When considering potential mechanisms of change for their mindfulness intervention, Thompson et al noted that the athletes in the mindfulness group experienced statistically significant increases in their ability to function with awareness and in their overall levels of trait mindfulness, while similarly experiencing statistically significant decreases in task-relevant worries and task-irrelevant cognitions. In another recent RCT of a mindfulness-based program (Jekauc, Kittler, & Schlagheck, 2017), the effectiveness of Berlin mindfulness-based training for athletes was compared with a traditional sport psychology inter vention. In the study, 22 individuals took part in the mindfulness group, and 24 individuals took part in the traditional intervention.…”
Section: Direct Mindfulness-based Intervention Studiesmentioning
confidence: 99%